Clinical Outcomes Based on the Attainment of Low-Density Lipoprotein Cholesterol Targets in Patients with Acute Coronary Syndrome in Real-World Practice - Wei-Chieh Lee; Yi-Hsuan Tsai; Yun-Yu Hsieh; Yen-Nan Fang; Chih-Yuan Fang; Po-Jui Wu; Huang-Chung Chen; Ping-Yen Liu; Hsiu-Yu Fang (International Journal of Clinical Practice)
Objective. A target of low-density lipoprotein cholesterol (LDL-C) <70 mg/dL or ≥50% reduction should be set. This study aimed to explore the information required to attain the optimal goal of lipid control for patients with ACS in real-world practice using big database analysis. Methods. Patients with ACS were enrolled between January 2005 and December 2019, and their medical history was obtained from the Chang Gung Research database. According to the attainment of LDL-C levels, the study population was divided into groups with and without ≥50% reduced LDL-C levels. In the group that achieved ≥50% reduced LDL-C levels, the study population was subdivided into groups with and without achievement of LDL-C level < 70 mg/dL. Results. This study enrolled 14,520 participants, out of whom only 3,367 patients (23.2%) achieved ≥50% reduced LDL-C levels. At the 3-year follow-up periods, higher incidences of cardiovascular (CV) mortality and all-cause mortality were absorbed in patients without ≥50% reduced LDL-C levels, especially in subgroups of hypertension and diabetes mellitus (DM). When comparing different percentages of reduced LDL-C levels, the significantly lowest hazard ratio (HR) of CV and all-cause mortality was noted at ≥50% reduced LDL-C levels (CV mortality; HR: 0.64; all-cause mortality; HR: 0.57). Conclusion. In the ACS population, better clinical outcomes were yielded in patients with ≥50% reduced LDL-C levels, especially in the hypertension and DM populations. However, strict lipid control did not show better clinical outcomes in patients with ≥50% reduction and <70 mg/dL in LDL-C levels.